The Nepohualtzintzin as a Teaching Strategy for the Development of Logical-Mathematical Intelligence in 8-Year-Old Children - Ipiales Bernal, Carla (Revista Ecos de la Academia, 2025)
The present study examines the impact of nepohualtzintzin, an ancestral calculation tool, on the development of logical-mathematical intelligence in 8-year-old children. It aims to evaluate its effectiveness in comparison with conventional teaching methods. The research adopts a pretest-post-test experimental approach, applying tests before and after the pedagogical intervention. Therefore, the sample consisted of 17 students from the Unidad Educativa Particular ‘Oviedo’ in Ibarra, Ecuador. During the process, the nepohualtzintzin was implemented as a manipulative didactic tool, integrating it into the teaching of basic mathematical operations. In this way, the results showed a significant increase in accuracy and speed in the resolution of calculations, demonstrating that the use of manipulative materials facilitates the understanding of abstract concepts and improves student motivation. From the teachers’ perspective, a general lack of knowledge about this ancestral tool was identified, although a favourable attitude towards its incorporation in the classroom was evident. In conclusion, the application of nepohualtzintzin not only optimises logical-mathematical thinking, but also promotes meaningful, contextualised and culturally enriching learning. To ensure its effective implementation, continuous teacher training and the integration of innovative methodologies within the school curriculum are recommended, thus favouring the diversification of pedagogical strategies and the improvement of academic performance in mathematics.